PENGARUH PEMBERDAYAN DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi Pada Biro Umum Setda Provinsi Jawa Tengah) - Farid Aly Ikhwan, 12.52.02.0228; Suko Priyono, Bambang (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the effect of Empowerment and, Quality of Work Life on the Performance of mediation Organizational Citizenship Behavior at Biro Umum of Central Java. The population is an employee of the agency as much as 305 employees, while the samples to be taken in this study of 173 respondents with a sampling method using proportional sampling. Research instrument used by questionnaire using Likert scale. The technique test data in this study includes testing instruments, test models, test hypotheses and test mediation. Based on the research that has been done, it can be seen that the empowerment of a positive and significant effect on Organizational Citizenship Behavior. Quality of work life of a positive and significant effect on Organizational Citizenship Behavior. Empowerment of a positive and significant effect on performance. Quality of work life of a positive and significant effect on performance. Organizational Citizenship Behavior of a positive and significant effect on performance. Mediation test results of Organizational Citizenship Behavior didnât mediated the effect of empowerment on the performance and also Organizational Citizenship Behavior didnât mediated the effect of quality of work life on the performance.Keywords: Empowerment, Quality of Work Life, Organizational Citizenship Behavior and Performance